Os verbos ser, estar, ter e haver no “Leal Conselheiro” de D. Duarte: Achegas para um quadro linguístico do século XV - Paulo, Osório; Lisete, Gaspar (Wydawnictwo Naukowe UAM, 2013)
Being a text of profound personal introspection, the Leal Conselheiro was born to give voice to King Duarte´s meditations on the real problems of human life and Portuguese people. His message was one of social projection and had a pedagogical purpose of national dimension, though it meant to cause an effect on the Portuguese moral and cultural identity that he wished to see guided by timeless principles of Christian nature. Created in the Middles Ages, the book will also be a testimony of change and innovation in place, especially because this is a moment of linguistic transition and emancipation in which new and old forms need to coexist. In this essay we will be particularly focused on the verbs ser, estar, haver and ter, observing their semantics and syntactic proximity, achieving a study that involves the intrinsic relation between ser / estar and haver / ter. We’ll analyse their evolution in order to explore common traces and meanings, but also the contexts that mark their individuality. Finally, we shall move towards the research provided by our corpus aiming at its quantitative and statistic treatment. We’ll define the behavioural traces that involve the variables studied and we’ll support the results on a specific group of syntactic and semantic criteria. Conclusively, according to the results, we’ll point to the years between 1428 and 1430 to mark the birth of the manuscript. Placed on the beginning of the middle archaic period, the text reveals mostly cases of variation of forms, not necessarily the total consummation of change.
Auxiliary verbs ser, estar, ter and haver in The Loyal Counsellor of Edward, King of Portugal. Towards a linguistic description of 15th century Portuguese
Keywords: historical linguistics; syntactic and semantic analysis of verbs SER, ESTAR, TER and HAVER; auxiliary verbs